Controls on Methane Occurrences in Shallow Aquifers Overlying the Haynesville Shale Gas Field, East Texas. Issue 4 (19th January 2017) - Nicot, Jean‐Philippe; Larson, Toti; Darvari, Roxana; Mickler, Patrick; Slotten, Michael; Aldridge, Jordan; Uhlman, Kristine; Costley, Ruth
Abstract: Understanding the source of dissolved methane in drinking‐water aquifers is critical for assessing potential contributions from hydraulic fracturing in shale plays. Shallow groundwater in the Texas portion of the Haynesville Shale area (13, 000 km 2 ) was sampled (70 samples) for methane and other dissolved light alkanes. Most samples were derived from the fresh water bearing Wilcox formations and show little methane except in a localized cluster of 12 water wells (17% of total) in a approximately 30 × 30 km 2 area in Southern Panola County with dissolved methane concentrations less than 10 mg/L. This zone of elevated methane is spatially associated with the termination of an active fault system affecting the entire sedimentary section, including the Haynesville Shale at a depth more than 3.5 km, and with shallow lignite seams of Lower Wilcox age at a depth of 100 to 230 m. The lignite spatial extension overlaps with the cluster. Gas wetness and methane isotope compositions suggest a mixed microbial and thermogenic origin with contribution from lignite beds and from deep thermogenic reservoirs that produce condensate in most of the cluster area. The pathway for methane from the lignite and deeper reservoirs is then provided by the fault system. Abstract : Article impact statement : Dissolved CH4 in aquifers over the Haynesville play is natural, sourced from shallow lignite beds and thermogenic reservoirs through faults.